Chemical composition and antioxidant activity of extracts from Moroccan fresh fava beans pods (Vicia Faba L.). - Adil Kalili; Rachida El Ouafi; Abdelghani Aboukhalaf; Kaoutar Naciri; Manal Tbatou; Seloua Essaih; Abdelmonaim Belahyan; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. In Morocco, fava beans are widely used as a main meal or as an ingredient in various traditional recipes, in the form of fresh ripe seeds or dry seeds. In the past, the tender skin of bean pods was also used in certain specific dishes, thus diversifying the diet. However, the peels of the tender bean pods are currently less or not used and considered waste. In Moroccan, fava bean pods peels, traditionally used in food in the past, are today considered as waste. The valorization of fresh fava bean pods could revitalize the use of the specific dishes and diversify the diet. For this reason, the research aimed to assess the nutritional values and biological compounds of the whole fresh fava bean pods (Vicia faba L.). Objective. Evaluate the content of nutrients, total phenolic, flavonoids and tannin contents and antioxidant activity in different extracts of the tender pods of the fava bean (Vicia faba L.). Material and methods. The proximate composition and minerals were determined using AOAC methods. The total phenolic compounds by the Folin-Ciocalteu reagent, the total flavonoids were analyzed using aluminum chloride colorimetric method, the tannins by method of vanillin in an acidic medium and the antioxidant activity was evaluated by DPPH method. Results. The results show that the fresh fava bean pods have a moisture content of 87.31 ± 0.25%, ash 4.67 ± 1.03, and protein 29.11 ± 3.20 g/100 g. The legume samples also contain potassium (1946.8±4.61), phosphorus (483.8 ± 3.14), and calcium (399.6 ±2.25) mg/100 g of dry matter representing at last 40-50% of the RDI. The content of the different extracts of (Vicia faba L) varied from 49.5 to 594.4 mg GAE/ g for the total phenols, from 0.7 mg to 3.4 mg QE/g for flavonoids, and from 4.9 mg to 73.91 mg TAE/g dry weight for tannins. The evaluation of the antioxidant activity in the various extracts revealed a better activity in the methanolic extract (IC50=491.2 μg/mL) compared to others extracts: the MeOH/water extract (IC50=606.61 μg/mL), DCM/ MeOH extract (IC50 = 642.67 μg/mL) and DCM extract below of 50%. Conclusions. This study shows that fava bean pods, traditionally used in food, are rich in macro and micronutrients and bioactive substances, which demonstrates their potential contribution to human food and nutritional security.